Volcanic hazard on Deception Island (South Shetland Islands, Antarctica) - Bartolini, Stefania; Geyer, Adelina; Martí Molist, Joan; Pedrazzi, Dario; Aguirre-Díaz, Gerardo (Journal of Volcanology and Geothermal Research, 2014)
Deception Island is the most active volcano in the South Shetland Islands and has been the scene of more than twenty identified eruptions over the past two centuries. In this contribution we present the first comprehensive long-term volcanic hazard assessment for this volcanic island. The research is based on the use of probabilistic methods and statistical techniques to estimate volcanic susceptibility, eruption recurrence and the most likely future eruptive scenarios. We perform a statistical analysis of the time series of past eruptions and the spatial extent of their products, including lava flows, fallout, pyroclastic density currents and lahars. The Bayesian event tree statistical method HASSET is applied to calculate eruption recurrence, while the QVAST tool is used in an analysis of past activity to calculate the possibility that new vents will open (volcanic susceptibility). On the basis of these calculations, we identify a number of significant scenarios using the GIS-based VORIS 2.0.1 and LAHARZ software and evaluate the potential extent of the main volcanic hazards to be expected on the island. This study represents a step forward in the evaluation of volcanic hazard on Deception Island and the results obtained are potentially useful for long-term emergency planning. This work was supported by the European Commission (FP7 Theme: ENV.2011.1.3.3-1; Grant 282759: VUELCO) and the MICINN grant CTM2011-13578-E. AG is grateful for her Juan de la Cierva Grant (JCI-2010-06092) and Ramón y Cajal contract (RYC-2012-11024). Peer reviewed